Longitudinal progesterone profiles in baleen from female North Atlantic right whales (Eubalaena glacialis) match known calving history - Hunt, Kathleen E. (Conserv Physiol, 2016)
Reproduction of mysticete whales is difficult to monitor, and basic parameters, such as pregnancy rate and inter-calving interval, remain unknown for many populations. We hypothesized that baleen plates (keratinous strips that grow downward from the palate of mysticete whales) might record previous pregnancies, in the form of high-progesterone regions in the sections of baleen that grew while the whale was pregnant. To test this hypothesis, longitudinal baleen progesterone profiles from two adult female North Atlantic right whales (Eubalaena glacialis) that died as a result of ship strike were compared with dates of known pregnancies inferred from calf sightings and post-mortem data. We sampled a full-length baleen plate from each female at 4 cm intervals from base (newest baleen) to tip (oldest baleen), each interval representing ∼60 days of baleen growth, with high-progesterone areas then sampled at 2 or 1 cm intervals. Pulverized baleen powder was assayed for progesterone using enzyme immunoassay. The date of growth of each sampling location on the baleen plate was estimated based on the distance from the base of the plate and baleen growth rates derived from annual cycles of stable isotope ratios. Baleen progesterone profiles from both whales showed dramatic elevations (two orders of magnitude higher than baseline) in areas corresponding to known pregnancies. Baleen hormone analysis shows great potential for estimation of recent reproductive history, inter-calving interval and general reproductive biology in this species and, possibly, in other mysticete whales.